IS THERE AN ASSOCIATION BETWEEN MYOPIA AND DRY EYE SYMPTOMS AMONG THE UNIVERSITY STUDENTS IN KUANTAN, MALAYSIA? - BINTI BADARUDIN, NOOR EZAILINA; BINTI ZOLKIFLI, NUR AUNI ATHYRAH (International Journal of Allied Health Sciences, 2023)
Introduction: Refractive errors may contribute to dry eye disease especially in myopia with the possible alterations in the corneal curvature, thickness and endothelial density as the eyeball elongates. However, the association between refractive errors and dry eye symptoms has not been fully investigated and the prevalence of myopia has yet to be identified among the university students in Kuantan, Malaysia. Methods: Eighty-three first year Kulliyah of Allied Health Sciences (KAHS) students of either myopes or emmetropes responded to two questionnaires namely the refractive error questionnaire to determine the refractive status, apart from undergoing a physical subjective refraction, and Ocular Surface Disease Index (OSDI) to determine their dry eye status via email, QR code and online messaging platform. The OSDI scores were compared between myope and emmetropes using Independent T-test and Spearman’s rank-order correlation analysis. Results: The prevalence of myopia among the first-year students was about 68%. In addition, 60.24% of year 1 KAHS students reported having dry eye symptoms but there was no significant association between refractive error and dry eye symptoms (p>0.05). However, OSDI scores were significantly higher in myopes compared to emmetropes (p<0.05). Conclusion: The estimated high prevalence of myopia among university students may be due to prolonged near work and usage of gadgets. OSDI score in myopia is higher compared to emmetrope which may be due to the changes that occur in the anterior surface of cornea.